An Efficient UPLC-MS/MS Method Established to Detect Relugolix Concentration in Rat Plasma - Xing, Liying; Liu, Ya-nan; Yao, Hongye; Wang, Tingting; Xie, Fuchen; Luo, Shunbin; Luo, Pingping; Tang, Shengling (Frontiers in Pharmacology, 2022)
Relugolix, a gonadotropin-releasing hormone (GnRH) receptor antagonist, has been well studied in the treatment of endometriosis symptomatic. It is mainly metabolized by the CYP3A subfamily of P450 enzymes, while minorly metabolized by CYP2C8. Daidzein in different dose groups exhibited a certain induction on the mRNA expression level of CYP3A4 and resulted in the potent induction of CYP3A4. However, it is still unknown whether daidzein and relugolix interact. We developed an effective ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method to study the effect of daidzein on the pharmacokinetics of relugolix in rats after oral administration of 12 mg/kg relugolix in a single or mixed of 50 mg/kg daidzein. The results showed that the method had respectable linearity (r2 > 0.999) on the scale of 0.7–1000 ng/mL. The intra-day precision was between 3.0% and 8.4% in this assay, and the inter-day was between 4.0% and 11.7%. The intra-day accuracy was from -4.3% to 6.1%, and the inter-day was 2.9% to 12.1%. Another three key indicators, including the stability, the recovery rate of extraction and the new technique’s matrix effect, were perfectly in accord with the test verification rule in the biological medium by the United States Food and Drug Administration. Meanwhile, treatment with daidzein led to a decrease in Cmax and AUC0–t of relugolix by about 15.56% and 21.36%, respectively. Although there was no statistical difference in pharmacokinetic parameters, it reflected the induction trend of daidzein on relugolix metabolism for food-drug interaction. It would provide reference and improvement value for subsequent experiments.